TEORI KRITIS DAN RELEVANSINYA UNTUK PENGKAJIAN TERHADAP REALITAS SOSIAL BANGSA INDONESIA - Sermada Kelen Donatus (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2015)
This essay elaborates the Critical Theory proposed by a group of German intellectuals who revived the anti-capitalist social theory of Karl Marx. They belong to what is called the “Frankfurt-School” which emphasises the contextualisation of Marx’ theory. Critical Theory emerged as a response to anti-socialist dominance in contemporary society. This essay takes up some of the ideas of Frankfurt-School members Max Horkheimer, Theodor Adorno, Herbert Marcuse and Jürgen Habermas. Critical Theory can impact greatly on how we read present-day Indonesian society which is being destroyed by the global capitalist-system which in turn is producing social diseases like systemic corruption. Keywords: Teori Kritis, sekolah Frankfurt, Karl Marx, Horkhmeimer, Adorno, Marcuse, Habermas, relevansi teori kritis, realitas sosial Indonesia.